(untitled) (Research, Society and Development, 2022)
Temporomandibular disorders are pathological conditions caused by various functional, physical and psychological factors. The symptoms presented are: facial pain, muscle pain, headache, bruxism, joint limitation and clicking. Today there are several therapeutic approaches, from the most conservative to the most invasive. Therefore, the objective of this study was to analyze the results of the use of acupuncture in the treatment of temporomandibular disorders. This work was elaborated from a review of narrative literature with a qualitative approach and descriptive character. The databases used were Google Scholar, PubMed, Lilacs and Medline. In the same vein, the current literature cites that acupuncture has been shown to be effective in the treatment of TMDs and in the analgesia of their associated pain. In addition, some research cites that dry needling therapy has shown positive patient responses. Based on the research carried out, it was evidenced that acupuncture is a positive form of treatment for patients, emerging as the main option or adjunct to conventional treatments. However, further studies with greater scientific rigor and randomized studies with a larger sample of patients are needed.